High prevalence of multidrug-resistant community-acquired methicillin-resistant staphylococcus aureus at the largest veterinary teaching hospital in Costa Rica - Rojas, Irene (2017)
Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogen associated with severe infections in companion animals present in the community, and it is diagnosed in animals admitted to veterinary hospitals. However, reports that describe the circulation of MRSA in animal populations and veterinary settings in Latin America are scarce. Therefore, the objective of this study was to determine the prevalence and investigate the molecular epidemiology of MRSA in the environment of the largest veterinary teaching hospital in Costa Rica. Preselected contact surfaces were sampled twice within a 6-week period. Antimicrobial resistance, SCCmec type, Panton-Valentine leukocidin screening, USA type, and clonality were assessed in all recovered isolates. Overall, MRSA was isolated from 26.5% (27/102) of the surfaces sampled, with doors, desks, and examination tables most frequently contaminated. Molecular analysis demonstrated a variety of surfaces from different sections of the hospital contaminated by three highly related clones/pulsotypes. All, but one of the isolates were characterized as multidrug-resistant SCCmec type IV-USA700, a strain sporadically described in other countries and often classified as community acquired. The detection and frequency of this unique strain in this veterinary setting suggest Costa Rica has a distinctive MRSA ecology when compared with other countries/regions. The high level of environmental contamination highlights the necessity to establish and enforce standard cleaning and disinfection protocols to minimize further spread of this pathogen and reduce the risk of nosocomial and/or occupational transmission of MRSA.